1979
DOI: 10.1177/00220345790580024501
|View full text |Cite
|
Sign up to set email alerts
|

Matrix - Mineral Relationships in Enamel Tissues

Abstract: A personal view of vertebrate enamels and their matrix-mineral relationships is given by first considering enamel types and speculating on the nature, distribution, formation and role of enamel protein. Not all the work consulted is mentioned in the text. The additional works are, however, included in the list of references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Several studies suggested that elasmobranch enameloid was the primitive hard tissue that appeared before enamel and that the relationship between the two is directly homologous (Fearnhead, 1979;Goto, 1976Goto, , 1987Moss, 1970Moss, , 1977. In contrast, it was suggested that elasmobranch enameloid is distinct from enamel and that the enameloid found in living fish is not an ancestral hard tissue of enamel, but rather an analog (e.g., Sasagawa and Ishiyama, 1999).…”
Section: Relationship Between Enameloid and Enamelmentioning
confidence: 99%
“…Several studies suggested that elasmobranch enameloid was the primitive hard tissue that appeared before enamel and that the relationship between the two is directly homologous (Fearnhead, 1979;Goto, 1976Goto, , 1987Moss, 1970Moss, , 1977. In contrast, it was suggested that elasmobranch enameloid is distinct from enamel and that the enameloid found in living fish is not an ancestral hard tissue of enamel, but rather an analog (e.g., Sasagawa and Ishiyama, 1999).…”
Section: Relationship Between Enameloid and Enamelmentioning
confidence: 99%
“…T he function of enam el m a trix is p ro b ab ly m ore com plex as, due to the fact th at only b ru sh ite nuclei are fo rm ed , this m atrix m ust at least inhibit th e form ation of O C P nuclei from the enam el fluid which is su p e rsa tu rate d b o th with O C P and w ith bru sh ite. C ertainly, th e en am el m atrix allows for the form ation of the needle-like brushite crystals [43][44][45] in p ro b ab ly the sam e way as colla gen allows for O C P nu cleatio n , i.e. it acts prim arily as a m echanical b arrier leading to a lim ited form and size of th e crystals [43] ra th e r than as an agent p ro m oting th e h etero g en eo u s nucleation of brushite.…”
Section: Discussionmentioning
confidence: 99%
“…C ertainly, th e en am el m atrix allows for the form ation of the needle-like brushite crystals [43][44][45] in p ro b ab ly the sam e way as colla gen allows for O C P nu cleatio n , i.e. it acts prim arily as a m echanical b arrier leading to a lim ited form and size of th e crystals [43] ra th e r than as an agent p ro m oting th e h etero g en eo u s nucleation of brushite. In any w ay, th e m ost p red o m in an t role of the m atrix seem s to be th a t of a spatial constriction and o rien tatio n .…”
Section: Discussionmentioning
confidence: 99%
“…The resultant of these features provide for species-specific enamel crystal patterns in enameloid of sharks and bony fishes as well as the enamel of newts, crocidiles, rabbits, and mice (Boyde, 1995;Greenberg et al, 1983;Kawasaki and Fearnhead, 1983). Arguably, although the morphological phenotype of enamel varies between species, a common plan of developmental processes and their control are present within all vertebrate species that express enamel organ epithelial-derived extracellular matrix formation (see Fearnhead, 1979;Kallenbach and Piesco, 1978;Osborn, 1973;Piesco, 1979;Piesco and Kallenbach, 1985).…”
Section: Phylogenetic Features Of Enameloid and Enamel Biomineralizatmentioning
confidence: 99%